Ethnotaxonomy of sharks by expert fishers from South Bahia, Brazil: Implications for fisheries management and conservation - Barbosa Filho, Márcio Luiz Vargas; Ramires, Milena; Mourão, José da Silva; Rosa, Ricardo de Souza; Alves, Rômulo Romeu da Nóbrega; Costa-Neto, Eraldo Medeiros (Ethnobiology and Conservation, 2020)
Historically, Brazilian fisheries management has not considered the knowledge of fish taxonomy from within fishing communities. This study points out processes of recognition, classification and nomenclature of sharks achieved by fishermen from South Bahia, Brazil. Data were obtained through semistructured interviews visually stimulated by exhibiting images of 30 species of elasmobranch fishes. Regionally, elasmobranch species are inserted into the folk taxon called “leather fishes" and in a category known as “cação" (shark) family. In addition to hierarchical classification, the fishermen organize shark species by adopting an ethnodimorphic and sequential model based on ethnoontogeny. Ethnodiagnostic characteristics are mainly related to the morphology, ecology and even physiology of a species. A total of 144 epithets is recorded, with a mean value of 4.8 ethnospecies for each scientific correspondent. Richness of vernacular names impedes species-specific information gathering regarding shark landings if fisher knowledge is not considered and applied in the improvement of fisheries data. Thus, this study encourages the employment of fishermen as parataxonomists in order to assist in the identification of sharks to specific levels. This study further emphasizes the potential of using ethnotaxonomic knowledge of fishing communities in initiatives related to participative management of shark fisheries in developing countries.